Associations of the Healthy Eating Index-2010 with risk of all-cause and heart disease mortality among adults with hypertension: Results from the National Health and Nutrition Examination Survey 2007–2014 - Zhang, Yuhui; Li, Duanbin; Zhang, Haizhu (Frontiers in Nutrition, 2023)
Background:Studies regarding the impact of Healthy Eating Index2010(HEI-2010) on the mortality of adults with hypertension are lacking. Objectives:To prospectively explore the relationships of HEI-2010 with mortality from heart disease and all causes in adults with hypertension based on the National Health and Nutrition Examination Survey (NHANES)2007-2014. Methods:This prospective cohort study included 6690 adults with hypertension from NHANES (2007– 2014). National Death Index data through 31 December 2019 was used to determine the amount of deaths due to heart disease and all other causes.We evaluated Hazard ratios (HRs) and 95% confidence intervals(CIs) using Cox proportional hazards models. Results: A total of 1259 deaths from all causes, including 338 due to heart disease, were documented over an average follow-up of 8.4 years..In comparison with the lowest quartile of HEI-2010 scores, multivariable-adjusted HRs (95% CIs) for all-cause mortality were 0.82(0.70,0.97), 0.78(0.64,0.95), and 0.68(0.54,0.85) for the second, third, and fourth quartiles of the HEI-2010 scores ( P-trend<0.001 ), as for heart disease mortality were 0.60(0.44,0.81), 0.59(0.40,0.89),and 0.53(0.35,0.80) (P-trend=0.010). Each increment in natural-log-transformed HEI-2010 scores was linked to a 43% reduction in the risk of all-cause mortality (P<0.001) and a 55% reduction in the risk of heart disease mortality (P =0.003).Among the 12 components of HEI-2010, adherence to higher intake of greens and beans, vegetables, total protein foods ,seafood and plant proteins, and unsaturated fatty acids ,as well as moderate consumption of empty calories, were related to a 21-29% lower risk of all-cause mortality. Conclusions:In the current study, there was a statistically significant inverse relationship between HEI-2010 and mortality from heart disease and all causes among adults with hypertension.Based on the findings,it may be helpful in guiding the dietary intake for adults with hypertension.